Flora of the montane rainforest and its relationship with environmental variables, in the Turquino National Park from Cuba - Rivero Herrada, Marisol (2018)
The work was carried out in two Zonal Conservation Units of the Turquino National Park, with the objective of relating the presence and distribution of the flora with the environmental variables in the Montane rainforest. For this, 70 plots of 100 m2 were established, distributed in seven sites, under a random sampling where all individuals with more than 5 cm of normal diameter were recorded. To determine the incidence of environmental variables in the distribution of the flora, in each unit of sampling: organic matter, thickness of the litter layer, altitude, slope, pH, canopy cover and anthropization were determined; likewise, an Analysis of Correspondence without Trend was carried out as an exploratory analysis, and then the direct ordering was carried out by means of a Canonical Correspondence Analysis, to obtain the distribution of the species with respect to the environmental variables. To determine the significance of the analysis, the Monte Carlos permutations test was applied. As results, it was obtained that in the evaluated altitudinal gradient 74 species of 66 genera and 42 families are reported, highlighting the presence of five endemic species and seven threatened species, in addition to nine species, of eight genus and seven families, denoting a high floristic diversity , as well as that the flora of the forest responds to the variations of the environment, being the descriptive variables of the relief, action of man and fertility of the soil those of greater contribution, from the ecological point of view, to the segregation of the distribution of the species.